Pengembangan Manajemen SDM Yang Berbasis Pada Kebutuhan Masyarakat Dan Pengembangan Kapasitas Pengelolaan Sumber Daya Manusia Di LPM Kelurahan Pamulang Barat - Andri Priadi; Shelby virby; Senen; Rizaldi, Muhamad (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2025)
This community service aims to analyze the role and function of Community Empowerment Institutions (LPM) in supporting the implementation of the East Pamulang Village work program. LPM functions as a bridge between sub-district government and the community in designing and implementing empowerment programs in various fields, such as economic, social, educational and infrastructure. The methods used in this activity include interviews, field observations, and focus group discussions to comprehensively identify the role of LPM. The results of the service show that LPM plays a significant role in encouraging community participation and ensuring that sub-district work programs are in line with the needs and aspirations of residents. However, there are several challenges, such as limited resources and community participation that still need to be improved. Therefore, it is recommended to increase the capacity of LPM through training and collaboration with various parties to support the effectiveness of sustainable community empowerment programs. Keywords: Management function, Performance